Medicinal plants used in traditional bone setting by the Khasi tribe of Meghalaya, India - Hinge, Lakhon M; Ana, Risso; Imlikumba; Talom, Duman; Rochill, Inubo; Bawri, Amal; Teron, Robindra (Plant Science Today, 2025)
Meghalaya is one of the 8 states of Northeastern India; it is known for its scenic beauty, unique culture, vibrant traditions and rich bio-diversity. Traditional bone setting is a field of study that focuses on ancient methods of treating bone fractures and joint dislocations, often practiced by traditional healers. This ancient art of healing fractures and musculoskeletal injuries has been passed down through generations, blending indigenous knowledge with practical experience. Conservation initiatives should also encourage the local communities to ensure sustainable practices that benefit both nature and people. The purpose of this study was to identify, document and preserve knowledge about the medicinal plants used in traditional bone settings by the Khasi tribe of Meghalaya. The data for the ethnobotanical study were collected by interviewing the traditional bone setters through a pre-structured questionnaire. Through extensive field surveys and interviews with 115 traditional bone setters, a total of 85 medicinal plant species (belonging to 44 families) were recorded. The Zingiberaceae family contributed the most species with 11 species, followed by Asteraceae with 7 plant species and Urticaceae with 6 species, Acanthaceae, Fabaceae, Rubiaceae, Amaranthaceae and Plantiginaceae with 3 species each, while other species were represented by 2 and 1 species. More scientific investigation is required to validate the folk claims/medicine and further research and validation of these practices could lead to the development of alternative or complementary therapies for bone-related ailments.